Perspectives on Malaysia's lack of implementation of green back lanes - Mahamod, Lukman Hakim; Ab Rahman, Syakir Amir; Bajrai, Aaliyah (Malaysian Institute of Planners, 2021)
Malaysia has been utilising green back lanes since the ‘90s. In spite of the several benefits of these lanes, such as the formation of active spaces, decrease in runoff water, and visitor attractions, green back lanes are yet to be deployed in the residential regions of Malaysia, prompting the question as to why these lanes have not yet been installed extensively. The objectives of this research work were: to determine what experts opined regarding the installation of green back lanes in the country, study the scenarios which caused the absence of implementation, produce a report showing the outcomes and analysis, and offer suggestions. The researcher deployed the interview strategy for ascertaining the views and standpoints of architects, town planners, maintenance staffs, project managers, and marketers on the dearth of green back lane installation. The research emphasises on the aspects of cost, maintenance, and safety.